Epidemiology and genetics of common mental disorders in the general population: the PEGASUS-Murcia project. Issue 12 (3rd December 2013) - Navarro-Mateu, Fernando; Tormo, MJ; Vilagut, G; Alonso, J; Ruíz-Merino, G; Escámez, T; Salmerón, D; Júdez, J; Martínez, S; Navarro, C
Abstract : Background: Multidisciplinary collaboration between clinicians, epidemiologists, neurogeneticists and statisticians on research projects has been encouraged to improve our knowledge of the complex mechanisms underlying the aetiology and burden of mental disorders. The PEGASUS-Murcia (Psychiatric Enquiry to General Population in Southeast Spain-Murcia) project was designed to assess the prevalence of common mental disorders and to identify the risk and protective factors, and it also included the collection of biological samples to study the gene–environmental interactions in the context of the World Mental Health Survey Initiative. Methods and analysis: The PEGASUS-Murcia project is a new cross-sectional face-to-face interview survey based on a representative sample of non-institutionalised adults in the Region of Murcia (Mediterranean Southeast, Spain). Trained lay interviewers used the latest version of the computer-assisted personal interview of the Composite International Diagnostic Interview (CIDI 3.0) for use in Spain, specifically adapted for the project. Two biological samples of buccal mucosal epithelium will be collected from each interviewed participant, one for DNA extraction for genomic and epigenomic analyses and the other to obtain mRNA for gene expression quantification. Several quality control procedures will be implemented to assure the highest reliability and validity of the data. This article describes the rationale, sampling methods and questionnaire content as well as the laboratory methodology. Ethics and dissemination: Informed consent will be obtained from all participants and a Regional Ethics Research Committee has approved the protocol. Results will be disseminated in peer-reviewed publications and presented at the national and the international conferences. Discussion: Cross-sectional studies, which combine detailed personal information with biological data, offer new and exciting opportunities to study the gene–environmental interactions in the aetiology of common mental disorders in representative samples of the general population. A collaborative multidisciplinary research approach offers the potential to advance our knowledge of the underlying complex interactions and this opens the field for further innovative study designs in psychiatric epidemiology.